LAW ENFORCEMENT AGAINST THE CRIMINAL ACT OF ILEGALLY IMPORTING THRIFT CLOTHES IN INDONESIA - Hafis Vivaldi Akbar; Dedy Saputra; Zarah Fathia (UNES Law Review, 2023)
The activity of illegally importing Thrift clothing in Indonesia seems to have become a pattern of life along with law enforcement actions that are less effective in overcoming criminal acts. This study aims to (1) find out the portrait of law enforcement against the criminal act of smuggling Thrift clothes in Indonesia; (2) to find out the factors causing the investigation into the alleged criminal act of smuggling Thrift clothing not to be carried out; and (3) knowing how to apply the law in law enforcement against the criminal act of smuggling Thrift clothes in Indonesia. This type of research is sociological legal research by exploring in depth the criminal act of importing thrift clothes illegally in Indonesia, especially in Indragiri Hilir district. The results of this study indicate that (1) law enforcement against the crime of smuggling Thrift clothing in Indonesia includes preventive and repressive measures; (2) the factors causing the investigation not to be carried out because the evidence was destroyed before entering the investigation stage; and (3) Law enforcement against the crime of clothing smuggling committed by Customs and Excise Civil Servant Investigators is not yet in accordance with statutory regulations.